REGULASI KEPROTOKOLAN NASIONAL DAN PRAKTIK KEPROTOKOLAN BERBASIS BUDAYA LOKAL: TELAAH LITERATUR KUALITATIF - Hasbi, Pebri Purnama; Sugiyanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This article aims to analyze the relationship between national protocol regulations and local culture-based protocol practices through a qualitative literature review approach. National protocol regulations, particularly Law of the Republic of Indonesia Number 9 of 2010 on Protocol, serve as formal guidelines for the organization of seating arrangements, ceremonial procedures, and forms of official respect in state and governmental events. However, in practice, the implementation of these regulations often interacts with deeply rooted local cultural values within traditional institutions and social structures. This study employs a qualitative literature review method by examining scholarly articles, books, and policy documents published within the last five years. A thematic analysis is applied to identify patterns of integration, adaptation, and potential tensions between formal legal norms and culture-based protocol practices. The findings indicate that national protocol regulations allow a degree of flexibility in their implementation, enabling contextual adaptation to local cultural practices as long as they do not conflict with legal principles and state interests. This study highlights the importance of a contextual approach to protocol implementation in order to maintain a balance between administrative order and the preservation of local cultural values.